A multi-layered network model identifies Akt1 as a common modulator of neurodegeneration - Na, Dokyun; Lim, Do-Hwan; Hong, Jae-Sang; Lee, Hyang-Mi; Cho, Daeahn; Yu, Myeong-Sang; Shaker, Bilal; Ren, Jun; Lee, Bomi; Song, Jae Gwang; Oh, Yuna; Lee, Kyungeun; et al. (EMBO Press, 2023)
The accumulation of misfolded and aggregated proteins is a hallmark of neurodegenerative proteinopathies. Although multiple genetic loci have been associated with specific neurodegenerative diseases (NDs), molecular mechanisms that may have a broader relevance for most or all proteinopathies remain poorly resolved. In this study, we developed a multi-layered network expansion (MLnet) model to predict protein modifiers that are common to a group of diseases and, therefore, may have broader pathophysiological relevance for that group. When applied to the four NDs Alzheimer's disease (AD), Huntington's disease, and spinocerebellar ataxia types 1 and 3, we predicted multiple members of the insulin pathway, including PDK1, Akt1, InR, and sgg (GSK-3 beta), as common modifiers. We validated these modifiers with the help of four Drosophila ND models. Further evaluation of Akt1 in human cell-based ND models revealed that activation of Akt1 signaling by the small molecule SC79 increased cell viability in all models. Moreover, treatment of AD model mice with SC79 enhanced their long-term memory and ameliorated dysregulated anxiety levels, which are commonly affected in AD patients. These findings validate MLnet as a valuable tool to uncover molecular pathways and proteins involved in the pathophysiology of entire disease groups and identify potential therapeutic targets that have relevance across disease boundaries. MLnet can be used for any group of diseases and is available as a web tool at . imageMLnet is a multi-layered network expansion model that finds proteins with pathophysiological relevance for groups of diseases. Application to four neurodegenerative diseases predicts multiple members of the insulin pathway as common modifiers.MLnet uses data integration and a multi-layered network expansion model to identify and prioritize for experimental testing proteins that affect pathophysiology across multiple diseases.When applied to Alzheimer's disease, Huntington's disease, and spinocerebellar ataxia types 1 and 3, MLnet identifies multiple members of the insulin pathway, proteostasis machinery and microtubule apparatus as common modifiers.The impact of the identified genes on neurodegenerative disease phenotypes is tested in Drosophila, human cell lines and mouse disease models.MLnet is available at and can be used for any group of diseases. MLnet is a multi-layered network expansion model that finds proteins with pathophysiological relevance for groups of diseases. Application to four neurodegenerative diseases predicts multiple members of the insulin pathway as common modifiers.image